A Strategic Analysis in Dynamic Random Access Memory Industry in Taiwan - Chen, Yen-Chun (2009)
The credit crisis and global economic recession have severely impacted on Integrated Circuit (IC) industry particularly in Dynamic Random Access Memory (DRAM) industry. The average selling price declined below the cost of chip and almost all memory producers are lack of cash flow. One of the global three 3 producers has been driven out of this industry and all Taiwanese DRAM vendors are facing to a dilemma on how they can survive through the economic recession and oversupply circumstance. This paper used Porter’s five forces analysis framework to examine the power of suppliers and buyers, threat of substitutes, potential entrant, and market penetration and strategies from each competitor and then applied the Resource-Based View to analyse the current Taiwanese resources with competitive advantages.